Comparative Analysis of NF-kappa B it the MyD88-Mediated Pathway After Implantation of Titanium Alloy and Stainless Steel and the Role of Regulatory T Cells - OKTAR, FAİK NÜZHET (ELSEVIER SCIENCE INC, 2020)
OBJECTIVE: Development of immunologically smart implants, integrated to biological systems, is a key aim to minimize the inflammatory response of the host to biomaterial implants. METHODS: The aim of this study is to investigate the influence of titanium alloy and stainless steel implants on immunological responses in rats by comparative analysis of nuclear factor kappa B (NF-kappa B) profiles in the activation of inflammatory signaling pathways and the role of CD4+CD25+Foxp3+. RESULTS: Both Ti alloy and stainless steel alloy group implantation affect Toll-like receptors-4 pathways and CD4+CD25+ regulatory T cells in different ways. CONCLUSIONS: Results show that NF-kappa B/p65 and NF-kappa B1/p50 possess potential as a therapeutic target in the prevention of adverse reactions to metal, especially for controlling inflammation after the implantation.
Keywords: Immunology; Inflammatory signal; Instrumentation; Metal implant; NE-kappa B profile; Spinal surgery; TOLL-LIKE RECEPTORS; LIPOPOLYSACCHARIDE; INFLAMMATION